The City “Amēdi” in Neo-Assyrian Texts - Nurgül YILDIRIM (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
From the begining of the first milennium BC I. Aramean which had begun to establish principalities in the Syria, Euphrates valley and the fertile lands in the south of Mesopotamia, also established Bīt-Zamāni principality whose capital was the city of Amēdi in the Diyarbakır region. Aramean principalities constituted a serious threat to the Assyrian Empire which was an important power of the period. For this reason, the kings of Assyrian organized expeditions to Aramean tribes. These expeditions were mentioned under a record in the annuals of kings. The annuals of Neo-Assyrian kings are the most reliable records to explain the structure of political and geographical structure of the period. This study aims to explore the city of Amēdi in the light of the NeoAssyrian annuals of kings, letters and inscriptions.